2018
DOI: 10.1021/jacs.8b10136
|View full text |Cite
|
Sign up to set email alerts
|

Design and Biosynthesis of Dimeric Alboflavusins with Biaryl Linkages via Regiospecific C–C Bond Coupling

Abstract: Alboflavusins (AFNs) are a group of cyclohexapeptides with moderate antibacterial and antitumor activities from Streptomyces alboflavus sp. 313. In vivo and in vitro studies proposed that AFNs are biosynthesized by a nonribosomal peptide synthetase machinery, and the 6-Cl-L-Trp precursor is supplied by a tryptophan halogenase gene located outside the afn gene cluster. Guided by the structure–activity relationship knowledge about the AFN-like cyclohexapeptides, two dimeric AFNs (di-AFNs) with regiospecific biar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…The results revealed that the introduction of exogenous RpsL (P91S) was key to the activation of 3 and 4. Next, the biological activities of 3 and 4 were assayed, 37 with daptomycin as a control (Table 1). Both compounds exhibited the capabilities of killing tested Gram-positive bacteria and fungal pathogens but not Gram-negative bacteria.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The results revealed that the introduction of exogenous RpsL (P91S) was key to the activation of 3 and 4. Next, the biological activities of 3 and 4 were assayed, 37 with daptomycin as a control (Table 1). Both compounds exhibited the capabilities of killing tested Gram-positive bacteria and fungal pathogens but not Gram-negative bacteria.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Alboflavusin is an analogue of the dimeric non-ribosomal peptide (NRP) anti-tumor agent and apoptosis inducing agents, himastatin and chloptosin. 75 Though less common so far, 5-chlorotryptophans may also be seen as motifs in natural products. Examples include the antibiotic pyrroindomycin B 27; the first step in the biosynthesis of this compound is the generation of 5-chlorotryptophan by PyrH.…”
Section: Mechanisms For Biocatalytic Halogenationmentioning
confidence: 99%
“…Alboflavusin is an analogue of the dimeric non-ribosomal peptide (NRP) anti-tumor agent and apoptosis inducing agents, himastatin and chloptosin. 75 …”
Section: Introductionmentioning
confidence: 99%
“…313 . In 2018, Guo et al designed and synthesized two dimeric AFNs (di‐AFNs) with biaryl linkages via C–C bond coupling (Figure ). As anticipated, the di‐AFNs exhibited much better antitumor and antibacterial activities than their monomers (10‐100‐fold improvement of antibiotic activities).…”
Section: Strategies To Develop Cyclic Peptides Into Therapeutic Agentsmentioning
confidence: 99%